Estudo clínico e etiológico da diarréia em potros - Olivo, Giovane [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Diarrhea is a serious problem in foals up to six months old, resulting in losses in equine business. The aims of this research were to perform the clinical study and the identification of main pathogens and virulence factors responsible for diarrhea in foals. A total of 56 foals with diarrhea (DG) and and 60 without diarrhea (CG) up to 90 days old were evaluated. Fecal samples of a (DG) and 60 without diarrhea (GC) up to 90 days old were evaluated. Hemogram and hemogasometry were performed in the animals of DG. Fecal samples of DG and GC were used to identify the enteropathogens. The main clinical findings in animals of GD were increased peristalsis and defecation frequency (100,%) and dehydration (67.8%). Hyperfibrinogenemia (26.8%), leukocytosis (12.5%), lymphocytosis (37.5%) and neutrophilia (17.8%), metabolic acidosis (16%) and decreased bicarbonate (16%) were the main hematologic findings. At least one of the enteropathogens studied was detected in DG (50/56) and in CG (48/60). In 32% (16/50) of positive samples was identified a single enteropathogen, while two or more enteropathogens were detected in 68% (34/50) of samples. E. coli showed the highest frequency in the isolations of foals with diarrhea (62.5%), followed by Salmonella spp. (25%); Strongyloides (25%); Strongyles (10.7%); C. perfringens (10.7%), Rhodococcus equi (7.1%); Cryptosporidium spp. (5.4%); C. difficile (1.8%), coronavirus (1.8), Giardia sp. (1.8%). In conclusion the identification of dehydrated animals and animals with severe electrolyte alterations as well as the need to detect the etiologic agents and their virulence factors are important to conduct the veterinarian to define control measures and appropriate therapy

A diarreia é um grave problema em potros até seis meses de vida, acarretando em prejuízos na equideocultura. Sendo assim os objetivos desta pesquisa foram realizar o estudo clínico e a identificação dos principais enteropatógenos e fatores de virulência, responsáveis pela diarreia em potros. Foram avaliados 56 potros com diarreia (GD) e 60 sem diarreia (GC) até 90 dias de vida. Foram realizados hemogasometria e hemograma dos animais do GD. Amostras fecais dos potros do GD e GC foram utilizadas para a identificação dos enteropatógenos. As principais alterações clínicas nos animais GD foram aumento da peristalse e da frequência de defecação (100,0%) e desidratação (67,8%). A hiperfibrinogenemia (26,8%), leucocitose (12,5%), linfocitose (37,5%) e neutrofilia (17,8), acidose metabólica (16%) e diminuição de bicarbonato (16%) foram os principais achados hematológicos. Ao menos um dos enteropatógenos pesquisados foi detectado no GD (50/56) e GC (48/60). Em 32% (16/50) das amostras positivas foi identificado um único enteropatógeno, enquanto que dois ou mais enteropatógenos foram detectados em 68% (34/50) das amostras. E. coli apresentou a maior frequência nos isolamentos dos potros com diarreia (62,5%), seguida da Salmonella spp. (25%); Strongyloides (25%); estrongilídeos (10,7%); Clostridium perfringens (10,7%); Rhodococcus equi (7,1%); Cryptosporidium spp. (5,4%); Clostridium difficile (1,8%); coronavírus (1,8%); Giardia sp. (1,8%). Conclui-se que a identificação dos animais desidratados e com graves alterações hidroeletrolíticas, bem como a necessidade de se detectar os agentes etiológicos e seus fatores de virulência, são importantes para direcionar o médico veterinário a definir medidas de controle e terapêutica adequados
Keywords: Equino - Doenças; Diarreia em animais - Diagnóstico; Virulencia (Microbiologia); Bacterias patogenicas; Diarrhea in animals